Ustanawianie i współpraca z centralnym zamawiającym - Wasiluk, Dominik (PRAWO i WIĘŹ, 2026)
To obtain the status of a central purchasing body, it is sufficient to meet the conditions specified in Art. 44 sec. 1 of the Public Procurement Law. The body appointing or designating the central purchasing body pursuant to Art. 47-49 of this Act should always instruct specific entities to use its services. It is not permissible to designate or appoint as the central purchasing body an entity that does not meet the conditions listed in Art. 44 sec. 1 of the Public Procurement Law. When the central purchasing body commences its activity, the condition for permanence of its operations should be assessed based on the entity's intention to conduct it in this manner. In most cases, entities interested in using the services of the central purchasing body are not obliged to conclude an agreement with it. Its conclusion will be advisable in the event of a voluntary entrustment of the award of a contract to the central contracting authority. The lawmaker should consider repealing sec. 2 and 3 of Art. 48 of the Public Procurement Law.